Comparative communication of health and hygiene awareness guides in Senegal: Dynamics and field realities - Sahite Gaye (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2026)
This article takes a close look at public health and cleanliness awareness campaigns in Senegal, unpacking how they’re shaped by local social representations and the persuasive communication techniques used by planners. The core question on the table: how effective are these guides—these campaigns, pamphlets, school programs, even cheeky SMS messages—at actually combating health threats like cholera and malaria, especially in the messiness of real-world cultural habits and beliefs? Methodologically, it is pretty robust—think: a “mixed-methods” approach, meaning the researcher didn’t just pluck stats from a spreadsheet. They got hands-on, analysing campaign content, running in-depth interviews, and even staking out actual initiatives to observe how people react in the wild. The analysis zeroes in on five significant Senegalese health efforts, such as “Marché Santé” (market-based health initiatives), “Écoles Santé” (school interventions), and the adrenaline-fueled Ebola SMS campaigns that bombarded communities during outbreaks. What did they find, as they combed through the data? Well, it’s not one-size-fits-all. Strategies ranged from top-down, didactic “here’s what you should do” messages, to more participatory, community-driven, and educational models. Interestingly, the notion of “cleanliness” itself turned out to be a hotbed of conflicting ideas—sometimes it’s framed in technical, almost clinical terms (use this soap, follow this routine), while elsewhere it’s enmeshed in the rhythms and traditions of local life (rituals, beliefs, even superstitions). The upshot of all this? If health guides are going to make real inroads, designers can’t just parachute in with generic solutions. Successful communication needs to be rooted in the everyday lives and cultural frameworks of specific communities. The article recommends, ultimately, that developers tailor health messaging more thoughtfully, integrating local practices and addressing the unique needs of each group. Only then is there any real hope of boosting health literacy and genuinely shifting everyday behaviours.